Household consumption through recent recessions - Thomas F. Crossley; Hamish Low; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2011)
This paper examines trends in household consumption and saving behaviour in each of the last three recessions in the UK. We identify several dimensions along which the most recent recession (the so-called 'Great Recession') has been different from those that occurred in the 1980s and 1990s. These include its depth and length as well as the composition of the cutbacks in expenditure - with a greater reliance on cuts to nondurable expenditure than was seen in previous recessions. We show that, both inside and outside recessions, the extent to which the growth in durable purchases is more volatile than growth in nondurable purchases has declined over the past 15 years. Finally, we present evidence that suggests that two aspects of fiscal policy in the UK in 2008 and 2009 - the temporary reduction in the rate of VAT and a car scrappage scheme - had some success in encouraging households to bring forward some durable purchases.
Keywords: E21; D12; 330; Consumption; Spending; Recessions; Konjunktur; Gesamtwirtschaftlicher Konsum; Sparen; Privater Haushalt; Finanzpolitik; Haushaltseinkommen; Großbritannien